Transcatheter Closure for Ventricular Septal Defect (VSD): Unveiling Key Predictors in Pediatric Interventions - Ria, Natal; Gunawijaya, Eka; Yantie, Ni Putu Veny Kartika (Jurnal Kardiologi Indonesia, 2025)
In “Transcatheter Closure for Ventricular Septal Defect (VSD): Unveiling Key Predictors in Pediatric Interventionse” (Indonesian Journal of Cardiology, 44(3), 95-102. https://doi.org/10.30701/ijc.1571), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1571. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1571